Jack Reacher : No Plan B - Book 27 - Child, Lee; Child, Andrew, 1968-; Brick, Scott (New York, New York : Penguin Random House Audio, 2022)
In Gerrardsville, Colorado, two witnesses to the same tragedy give two different accounts. One guy sees a woman throw herself in front of a bus in what authorities will call a suicide. The other witness is Jack Reacher. And he sees what actually happened: a man in a gray hoodie and jeans, moving like a shadow, pushed the victim to her death, before swiftly grabbing the dead woman's purse and strolling away. Reacher follows the killer on foot, not knowing that he's part of something much bigger and far-reaching: a secret conspiracy with many moving parts, with powerful people on the take, all involved in an undertaking that leaves no room for error
Keywords: Reacher, Jack -- (Fictitious character) -- Fiction; Retired military personnel -- Fiction; Murder -- Fiction. -- Investigation; Witnesses -- Fiction; Conspiracies -- Fiction; Criminals -- Fiction; FICTION / Thrillers / Suspense; FICTION / Action & Adventure; FICTION / Thrillers / Military; Colorado -- Fiction; Audiobooks; Thrillers (Fiction)